2018
DOI: 10.1021/acs.cgd.8b00740
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Transformation of Amorphous Nanoparticles into Crystalline Y Nanozeolites Using Poly(vinyl alcohol) Layers Covered onto the Amorphous Nanoparticles

Abstract: The Faujasite zeolite (Type-Y) is highly desired for many applications; nevertheless, these nanozeolites are challenging to synthesize via fast and low-cost pathways. This work provides a novel, simple, fast, and low-cost pathway to synthesize of Y nanocrystalline zeolite using poly­(vinyl alcohol) as a growth inhibitor. Poly­(vinyl alcohol) fasts the process transformation of amorphous particles into Y nanocrystalline zeolite through coating, protecting, and stabilizing of amorphous nanoparticles under high c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…and SiO 4 4− tetrahedral sharing oxygen atoms in their corners (Anbia et al, 2015;Anbia et al, 2017;Dehghan and Anbia, 2018;Garshasbi et al, 2017;Anbia, 2016, 2019). So far, many studies have been reported about the role of zeolites frameworks LTA (Linde Type A) and FAU (Faujasite) as builder in detergent formulations (Ayele et al, 2016;Cardoso et al, 2015a;Çulfaz, 1999;Donevska et al, 1985;Hui and Chao, 2006).…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation
“…and SiO 4 4− tetrahedral sharing oxygen atoms in their corners (Anbia et al, 2015;Anbia et al, 2017;Dehghan and Anbia, 2018;Garshasbi et al, 2017;Anbia, 2016, 2019). So far, many studies have been reported about the role of zeolites frameworks LTA (Linde Type A) and FAU (Faujasite) as builder in detergent formulations (Ayele et al, 2016;Cardoso et al, 2015a;Çulfaz, 1999;Donevska et al, 1985;Hui and Chao, 2006).…”
Section: mentioning
confidence: 99%
“…In these classes, zeolites are famous as eco‐friendly inorganic builders. In fact, zeolites, as well‐known micro‐porous molecular sieves with extensive catalytic, adsorptive, and ion‐exchange applications, possess many frameworks topologies formed by primary AlO 4 5− and SiO 4 4− tetrahedral sharing oxygen atoms in their corners (Anbia et al, 2015; Anbia et al, 2017; Dehghan and Anbia, 2018; Garshasbi et al, 2017; Koohsaryan and Anbia, 2016, 2019). So far, many studies have been reported about the role of zeolites frameworks LTA (Linde Type A) and FAU (Faujasite) as builder in detergent formulations (Ayele et al, 2016; Cardoso et al, 2015a; Çulfaz, 1999; Donevska et al, 1985; Hui and Chao, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…[25c] The interactions between the ZGMs and the growing zeolite framework can include van der Waals forces, electrostatic interactions, hydrogen bonding, and π-π stacking. [6,29] 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 the ZGM decreases the size of zeolite crystals because they act as colloidal stabilizer by adsorbing on crystal and/or precursor surfaces and inhibiting particle growth or attachment via steric stabilization, suppresses precursor aggregation and inhibits the kinetic rate of crystal growth. [26]…”
Section: Zeolite Growth Modifiermentioning
confidence: 99%